What are Fundamentals Rights? : A response from Humanist Constitutionalism - Caldera-Ynfante, Jesús E.; Rosell-Aiquel, Rafael (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2023)
It responds, from the dogmatics of the Colombian Constitutional Court, citing the normative “identification criteria” of fundamental rights focused on i) their relationship of functionality with the achievement of the normative content of human dignity, ii) their translation as subjective rights , iii) the “dogmatic, jurisprudential or international law, legal and regulatory consensus on its fundamentality” and, iv) its enforceability -more than its own justiciability-, as legal prerequisites recognition and constitutional pragmatic application in the sphere of life of the human person and the political community, also based on the conceptual pillars of the so-called Humanist Constitutionalism.